2005
DOI: 10.1007/s11201-005-6243-0
|View full text |Cite
|
Sign up to set email alerts
|

In situ generation of polyaniline in poly(dimethylsiloxane) networks

Abstract: Polyaniline (PANI) is one of the most studied and most stable electrically conductive polymers, with the conductive form being the navy blue emeraldine salt. However, PANI is very difficult to process and displays poor mechanical performance, which suggests improving its properties by developing composite systems. In the present approach, PANI was generated in situ in poly(dimethylsiloxane) (PDMS) networks. The color of the composites varied from brown, to blue, to greenish blue, with the blue samples being th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…For elastomeric polymers, considerable reinforcement can be obtained by generating a reinforcing filler in the polymeric matrix using the sol–gel approach because of the nature of the in situ precipitation which generates well‐dispersed particles having a strong interaction with the matrix. Mark and co‐workers8–10 used the sol–gel hydrolysis–condensation technique for the in situ generation of reinforcing silica, titania and zirconia within polydimethylsiloxane by accurate control of the required water of hydrolysis from the air and generating the required catalyst in situ from a tin salt. Well‐dispersed particles, good reinforcement and improved thermal stability as well as transparency were obtained in all cases.…”
Section: Introductionmentioning
confidence: 99%
“…For elastomeric polymers, considerable reinforcement can be obtained by generating a reinforcing filler in the polymeric matrix using the sol–gel approach because of the nature of the in situ precipitation which generates well‐dispersed particles having a strong interaction with the matrix. Mark and co‐workers8–10 used the sol–gel hydrolysis–condensation technique for the in situ generation of reinforcing silica, titania and zirconia within polydimethylsiloxane by accurate control of the required water of hydrolysis from the air and generating the required catalyst in situ from a tin salt. Well‐dispersed particles, good reinforcement and improved thermal stability as well as transparency were obtained in all cases.…”
Section: Introductionmentioning
confidence: 99%
“…LogðIÞ ¼ aLogðVÞ þ LogðGÞ where I, V, and G are the current, voltage, and conductance (G ¼ r x area=thick-ness) of the sample, respectively [66,67]. The results of these measurements are summarized in Table 4.…”
Section: DC Electrical Conductivity Measurementsmentioning
confidence: 99%
“…Although studies on the Fe 3 O 4 particles formation have been markedly advanced by the strenuous efforts of numerous researchers [13][14][15][16][17][18], the preparation and formation of ultrafine Fe 3 O 4 particles with narrow size distribution still remain as an open area for target drug therapy and medical imaging [19][20][21]. Previous studies have shown that metal ions have a tendency to form ionic clusters in a polymer matrix and exist as microphases that are separated by the hydrophobic portions of the polymers [22,23].…”
Section: Introductionmentioning
confidence: 99%